Adsorption dynamics of quercetin with electrospun konjac glucomannan fabric containing double stranded DNA. (16th January 2023) - Yoshiba, Kazuto; Kawada, Sara; Dobashi, Toshiaki; Yamamoto, Takao
Abstract: Konjac glucomannan nonwoven fabric containing double stranded DNA was fabricated by electrospinning to investigate the adsorption dynamics of quercetin. Insolubilization of the fabric was performed by immersing it in aqueous trisodium metaphosphate and NaOH solution. The time course of the adsorbed amounts of quercetin to the fabric was determined in water-ethanol mixtures with varying the quercetin concentration of the immersing solution and the DNA fraction. The theoretical analyses for the adsorption curves were performed with two theoretical equations based on the diffusion-limited dynamics, and the adsorption/desorption dynamics, respectively, to express the adsorption curves of quercetin to the electrospun fabrics. Two time constants and equilibrium adsorbed amounts of quercetin were discussed from their dependencies on the initial concentration of quercetin solutions, DNA content of the fabric, and the weight of the fabric. Graphical abstract: Image 1 Highlights: Quercetin was adsorbed by electrospun konjac glucomannan/DNA composite fabric. The amounts of adsorbed quercetin molecules increased with increasing the content of DNA. The adsorption behavior at the initial stage was dominated by diffusion process into the fabric. Kinetic adsorption/desorption was the rate-determining process of adsorption at the late stage.